Semantyka i symbolika „lasu” w poezji Zbigniewa Herberta - Tatarowski, Konrad W. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The word “forest” (plural “the forests were on fire”) starts the debut volume of Zbigniew Herbert. In all of his published poetry the word “forest” appears 54 times in 361 works in the published volume Poetry. “Forest” belongs to one of Herbert’s key words as interpreted by Kazimierz Wyka in his article “Key Words” that was published in 1969. Wyka adopted the term “key words” from the French critics Paul Guiraud and Gaston Bachelard.In Herbert’s poetry the word “forest” appears in a semantic form as an element of colloquial language (langue) as well as in a stylistic form that is characteristic of the poet’s individual language (parole) that constitutes an element of his poetic world.Through the analysis of a few of Herbert’s poems the author of the article points out the variety and wealth of the symbolic meanings of the word “forest” in all of the named poet’s poetry.